Peran Orang Tua Terhadap Perilaku Bullying di Sekolah Dasar - Febriati, Listia Dwi; Zakiyah, Zahrah; Ratnaningsih, Ester; Nugroho, Joko (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Indonesian Child Protection Commission explained in 2023, the most cases of child protection were victims of sexual crimes as many as 34.4%, followed by cases of physical and psychological violence as many as 14.3%. As many as 9.8% of cases of children facing legal cases. Child bullying in 2018 in Indonesia as many as 2 out of 3 girls or boys aged 13-17 years have experienced violence during their lives. The results of the study showed that more than 50% of elementary school students had experienced physical bullying at school, and only 37% of the 25 students answered that they had never experienced physical bullying, and those who experienced non-physical bullying were 49% and more than 50% of them had experienced non-physical bullying. One of the factors of bullying behavior based on research is the very lack of parental role. The results of a preliminary study at SD N 1 Jambidan showed that out of 10 responses, 9 respondents admitted that they had been bullied by classmates. The bullying behavior that often occurs is verbal, you are fat, thin, skinny and others. Physical behavior, some admitted to being pushed, smacked and slapped. Based on this, the purpose of this study is: to determine the influence of the role of parents on bullying behavior in children at SD N 1 Jambidan. Research method : Quantitative research with a Cross Sectional approach . The sampling technique is purposive sampling with a sample size of 100 respondents. Univariate data analysis with frequency distribution, Bivariate analysis with the Kendall Tau test . Research Results : The results of the Kendall Tau analysis obtained a p value of 0.000 with a relationship strength of 0.645 and a positive relationship direction. Conclusion : There is an influence between the role of parents and bullying behavior in children at SD N 1 Jambidan. The better the role of parents, the more it minimizes bullying at school, and conversely, the less the role of parents, the more it affects the severity of bullying behavior at school.